Quality of life at initial presentation in patients with gynaecological malignancies: a cross-sectional study from a tertiary care centre in India - Chadha, Saloni; Chohan, Shikhar; Mishra, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Gynaecological malignancies are associated with significant physical, psychological, social, and functional morbidity, often beginning at the time of diagnosis. Quality of life (QOL) assessment at baseline remains underexplored in the Indian setting. This study aimed to evaluate the quality of life of patients with gynaecological cancers at the time of initial presentation using the Functional Assessment of Cancer Therapy-General (FACT-G) questionnaire. Methods: This cross-sectional observational study included 70 newly diagnosed, treatment-naïve patients with gynaecological malignancies presenting to a tertiary care hospital in North India. QOL was assessed using the interviewer-administered FACT-G questionnaire, comprising physical, social, emotional, and functional well-being domains. Descriptive statistical analysis was performed. Results: Pain was the most frequently reported physical symptom, affecting 73% of patients. Emotional distress was highly prevalent, with 78% reporting sadness and fear of dying. Social well-being was compromised, with 88% reporting lack of closeness to friends and 70% dissatisfaction with sexual life. Overall, 76% of patients were dissatisfied with their current quality of life. Conclusions: Quality of life was significantly impaired across multiple domains at the time of diagnosis of gynaecological cancers. Early identification of QOL deficits and integration of supportive and psychosocial care from the outset of cancer management are essential to improve patient-centered outcomes.